3D actuation of foam-core liquid metal droplets. Issue 7 (15th December 2022) - Chen, Yue; Chen, Xuanhan; Zhu, Zhenhong; Sun, Mingyuan; Li, Shen; Gan, Minfeng; Tang, Shi-Yang; Li, Weihua; Zhang, Shiwu; Sun, Lining; Li, Xiangpeng
Abstract : The foam-core liquid metal (FCLM) droplets that can maintain the surface properties of LM while significantly reducing the density are developed, enabling 3D manipulation in an electrolyte. Abstract : Precise manipulation of liquid metal (LM) droplets possesses the potential to enable a wide range of applications in reconfigurable electronics, robotics, and microelectromechanical systems. Although a variety of methods have been explored to actuate LM droplets on a 2D plane, versatile 3D manipulation remains a challenge due to the difficulty in overcoming their heavy weight. Here, foam-core liquid metal (FCLM) droplets that can maintain the surface properties of LM while significantly reducing the density are developed, enabling 3D manipulation in an electrolyte. The FCLM droplet is fabricated by coating LM on the surface of a copper-grafted foam sphere. The actuation of the FCLM droplet is realized by electrically inducing Marangoni flow on the LM surface. Two motion modes of the FCLM droplet are observed and studied and the actuation performance is characterized. Multiple FCLM droplets can be readily controlled to form 3D structures, demonstrating their potential to be further developed to form collaborative robots for enabling wider applications.